Understanding Numbers — Concepts and Some Misconceptions - PANT, POONAM; PANT, VYOMESH (THE PRIMARY TEACHER, 2016)
Interactions with students and teachers in NDMC schools reveal that there are some problems in the understanding of numbers during teaching-learning in classrooms. This paper tries to address the importance of numbers in mathematics, as well as, in our daily life. Though numbers are an essential part of our day-to-day life and mathematics cannot exist without numbers, students and teachers still have misconceptions about numbers. This paper attempts to discuss with the help of examples some of the problems faced by primary level children and teachers.